THEORETICAL SIGNIFICANCE OF THE STUDY OF SPEECH SKILLS IN FUTURE OFFICERS (American Journal of Interdisciplinary Research and Development, 2026)
The article is dedicated to highlighting the theoretical significance of studying speech mastery in future officers. The article allows for a review of several issues related to the content and organization of teaching disciplines related to speech culture in military educational institutions.